Pelagic whaling in the Antarctic : 7 : The season 1936-1937 - Hjort, Johan; Lie, J; Ruud, Johan T; Ottestad, Per (I kommisjon hos Dybwad, 1938)
Inneholder: A preliminary report on: Variations in the size distribution of Southern blue and fin whales by Per Ottestad
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Med kanon og kamera efter storhvalen - Slaattelid, Aasmund (Aschehoug, 1938)
Keywords: Sørishavet; fangst; hvalfangere; hvalfangst; pelagisk; sjøfolk

Hvalfangsten: et tilbakeblikk og en oversikt på grunnlag av norske patenter - Swensen, T (Teknisk ukeblad : Norges fremste på teknologi, 1938)
Keywords: Sørishavet; hvalfangst; patenter; pelagisk; teknologi

Biochemical studies of whaling problems : 1 - Valsø, Jakob; Pedersen, Torbjørn (I kommisjon hos Dybwad, 1938)
Inneholder: Jakob Valsø: The Hypophysis of the Blue Whale. (Balaenoptera musculus L.). Macroscopical and Microscopical Anatomy and Hormone Content. Torbjørn Pedersen: On the Course of Hydrogenation in the Industrial Hardening of Whale Oil with Nickel Formate Catalyst.
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; biokjemi; biologi; farmakologi; hvaler; hvalfangst; hvalolje; pelagisk